Factors Influencing Learning Outcomes in MYOB Accounting Computer Subject: A Study of Grade XI Accounting Students - Khairatuna'ilah, Khairatuna'ilah; Yuliati, Anik (Perkumpulan Dosen Muda (PDM) Bengkulu, 2025)
Purpose: This research aims to determine the partial influence of basic accounting knowledge, learning motivation, and computer knowledge on student learning outcomes in the MYOB Accounting Computer course. The study is important to identify key factors that support practical accounting skills and student readiness for the workforce. Methodology: A quantitative approach was applied using multiple linear regression analysis. The study employed a total sampling technique involving 133 Grade XI accounting students at a private vocational high school in Surabaya during the 2023/2024 academic year. Data were collected through documentation of MYOB course grades and questionnaires measuring the independent variables. Results: The analysis showed that basic accounting knowledge and learning motivation significantly influenced learning outcomes, while computer knowledge did not have a significant effect. Findings: The research highlights that foundational knowledge and intrinsic motivation are critical for students to succeed in applied accounting software learning. Novelty: This study offers a novel contribution by empirically examining the influence of cognitive factors such as basic accounting understanding, affective factors such as learning motivation, and technical factors such as computer knowledge on MYOB learning outcomes in a vocational school context. Unlike most previous studies that focus on higher education or isolate variables, this research provides a more integrated analysis relevant to the practical needs of vocational accounting education. Originality: The study reveals that computer knowledge alone does not ensure successful learning outcomes without the support of conceptual understanding and motivation, underlining the importance of integrated learning strategies. Conclusion: Enhancing basic accounting understanding and motivation is essential to improving MYOB learning outcomes. Type of Paper: Quantitative research paper.